Outcomes of corneal crosslinking for the treatment of keratoconus at a tertiary South African hospital - Kriek, Jozef (Division of Ophthalmology, 2023)
Objectives. To describe and analyse the effectiveness of using accelerated epithelium-off corneal crosslinking (A-CXL), in a cohort of patients with progressive keratoconus (KC), presenting to Groote Schuur Hospital, South Africa. Methods. A retrospective review of patients who underwent A-CXL, using 6.4 mW/cm2 ultraviolet-A irradiation for 15 min, for progressive KC between 1 May 2017 and 1 June 2018. All patients completed 6 months minimum follow-up (Mean 9months, range 6-15). The diagnosis of keratoconus was based on corneal tomography and its clinical signs. Keratometry values and visual acuities were measured to ascertain if there was improvement in acuity or corneal curvature at 6 months post-procedure. Results. Nineteen eyes of 17 patients were included. The group consisted of 6 (32%) males and 13 (68%) females, with a mean age of 22.17 years (SD = 5.8). Zero eyes showed mild keratoconus, 8(42%) showed moderate keratoconus and 11(58%) showed severe keratoconus. At 6 months follow-up, results revealed that UCDVA improved from logMAR 0.96 to 0.83 (p = 0.068) and BCVA improved from logMAR 0.40 to 0.34 (p = 0.073). The mean UCDVA and BCVA Snellen line gain was 0.43 and 0.94. Overall the change in UCDVA and BCVA trended towards being statistically significant. The median Kmax value decreased from 57.7D to 55.9D. The mean Kmax value decreased from 59.46D to 58.85D (p = 0.137). The mean Kmean anterior increased from 50.26D to 50.86D (p = 0.139), the mean Kmean posterior from -7.48D to -7.67D (p = 0.026). There was a statistically significant change in Kmean post, but not so for Kmean ant and Kmax. Both severity groups showed a decrease in thinnest point corneal pachymetry from mean 445 micrometer(μm) to mean 422 μm (Moderate: p = 0.009; Severe: p = 0.003). KC progression was stopped or stabilised in 13 eyes (68%); 6 eyes (32%) showed progression. No complications were found. Conclusions. Our results show the effectiveness of 15-minute A-CXL (irradiance of 6.4 mW/cm2) in maintaining both corneal stability and visual acuity in our patient population at 6 months follow-up. In future, a larger study with prolonged follow-up would be required to elucidate this finding.